Extracts of Artocarpus communis Decrease α-Melanocyte Stimulating Hormone-Induced Melanogenesis through Activation of ERK and JNK Signaling Pathways - Yi-Tzu Fu; Chiang-Wen Lee; Horng-Huey Ko; Feng-Lin Yen (The Scientific World Journal)
Artocarpus communis is an agricultural plant that is also used in folk medicine to prevent skin diseases, including acne and dermatitis. Extracts of A. communis have been used to effectively inhibit melanogenesis; however, the antimelanogenesis mechanism of these extracts has not yet been investigated. The present study utilized a cell-free tyrosinase assay as well as α-melanocyte stimulating hormone- (-MSH-) induced tyrosinase assay conducted in B16F10 cells, performed a cytotoxicity assay, and determined cellular melanin content to examine the effects of a methanolic extract of A. communis (ACM) and various organic partition fractions of A. communis on melanogenesis. In addition, we performed western blot analysis to elucidate the mechanism of their antimelanogenesis effect. Our results indicated that, except for the n-hexane extract, ACM and the various partition extracts at noncytotoxic concentrations effectively decreased melanin content and tyrosinase activity by downregulating microphthalmia-associated transcription factor (MITF) and phosphorylated cAMP response element-binding protein (p-CREB). Moreover, ACM and the partition fractions activated phosphorylation of extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) to inhibit the synthesis of MITF and finally to decrease melanin production. In conclusion, we suggest that noncytotoxic concentrations of ACM and the various partition fractions may be useful as references for developing skin-lighting agents for use in medicines or cosmetics.